Keabsahan Alat Bukti Surat Berupa Hasil Cetak Media Sosial dalam Perspektif Hukum Acara Perdata - Ekowati, Endang; Fatorina, Fetri; Mukhtarzain, Abdullah Akhmad; Asriana, Anisa Yuni (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
In civil procedural law, documentary evidence plays a central role. This evidence is not only in the form of authentic deeds or private deeds, but also includes other documents that can be used to prove the truth of a fact in court. The development of social media raises new issues regarding the validity of printouts from the platform as evidence. This is because social media is very susceptible to editing, manipulation, and digital engineering, which can ultimately raise doubts about the authenticity of the evidence submitted. The problem becomes more complex when evidence in the form of printouts from social media is submitted without a statement from a digital forensic expert. This research is a juridical-normative research. The approaches used are the legislative approach, the conceptual approach, and the case approach. The methods used in this research are library and documentation methods. The results of his research, the Regulations Governing Evidence of Letters in the Form of Printed Results from Social Media Until now are still contained in Article 164 HIR and Article 284 RBg, have not explicitly regulated evidence of letters in the form of printed results from social media. However, the existence of Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), which has been updated by Law Number 19 of 2016, provides recognition of the validity of electronic documents and their printouts as valid legal evidence. In addition, Supreme Court Regulation (PERMA) Number 1 of 2019 concerning Electronic Administration of Cases and Trials in Court also serves as a technical guideline in the use of electronic evidence. The validity of evidence in the form of printed results from social media depends on the judge's consideration based on the principle of free evidence (freies beweis system). The judge will assess the evidence based on its authenticity, integrity, relevance, and supported by other consistent evidence. While social media print evidence may be admissible without forensic expert testimony under certain circumstances, the presence of a digital forensic expert remains the ideal standard in complex cases, particularly to ensure the integrity of evidence that is susceptible to manipulation